FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN GIZI BURUK PADA BALITA DI WILAYAH KERJA PUSKESMAS GLOBAL LIMBOTO - Dewi Modjo; Euis Hidayat (program studi ilmu keperawatan fakultas ilmu kesehatan universitas muhammadiyah gorontalo, 2021)
The purpose of this study was to determine the relationship between exclusive breastfeeding, and Knowledge Economy Status with the incidence of malnutrition among children under five in Puskesmas Global Limboto Gorontalo district.This research method using analytic survey with case control approach.Using a statistical test Chi Square test using SPSS. Based on the results of research show that there is a relationship between Asi Exclusive (p = 0.001), Economic Status (p = 0.028) and knowledge (p = 0.009) in the incidence of malnutrition among children under five in Puskesmas Global Limboto Gorontalo district.